Floral characteristics of red-fleshed dragon fruit (Hylocereus polyrhizus) grown under Malaysia climate - C. L. Y., Joanna (International Society for Horticultural Science, 2022)
Red-fleshed dragon fruit was introduced into Malaysia since the late 1990s. Now, it has become one of the important fruit crops in the country. The floral characteristics of red-fleshed dragon fruit at pre-, during and post-anthesis was studied. The flower of red-fleshed dragon fruit is perfect, monoecious with both male and female organ in one flower and has a long floral tube of 27.8 cm in length. The flower perianth is formed by two types of tepals; the sepaloid tepals which covered the floral tube and the petaloid tepals which attached around the rim of the flower cup. The sepaloids are formed by 33 long ensiform yellow tepals and 25 greenish tepals of various shapes that ranged from ensiform to narrowly triangular. On the other hand, the petaloids are formed by 24 white lance-ovate inner tepals surrounded by 5 white-yellowish lanceolate outer tepals. The flowers are zygomorphic with the style and stamens located in the ventral part of the flower. The basifixed yellow anthers are borne on projecting yellow filaments with an average length of 8.04 cm. Stamens are found to be apostemonous with an average of 1016 stamens per flower. The length of filament and style of flower were about 8 and 27 cm, respectively. The spatial distance between stigma and anther was about 1.66 cm indicating the pistil was taller than the stamens. The flowers began to bloom in an upright position from 21:30 h and fully bloomed at 22:00 h. The flower remained blooming at 09:00 h the following morning and fully closed by 12:00 h. The pollinated flower eventually closed and started to wilt two days later. At 4 days after pollination, the flower had completely wilted, and fungi began to colonize the outer part of the flower and the browning extended to the style closest to the stigma.